KONSEP PENDIDIKAN BIRRUL WALIDAIN DALAM QS. LUQMAN (31): 14 DAN QS. AL â€" ISRA (17) : 23-24 - Fika Pijaki Nufus; Siti Maulida Agustina; Via Laila Lutfiah; Widya Yulianti (Universitas Islam Negeri Ar-Raniry, 2017)
Education Birrul Walidain is one of the most important factors in ideal character education. The creatoin of a generation that akhlakul karimah is a dream for the parents of their children. Education Birrul Walidain is very influential on adab to parents. In the Quâ€™an Allah has explained many related verses about Birrul Walidain. One of them is in sura Luqman verse 14 and sura Al â€" Isra verses 23-24. The word of God in sura Luqman verse 14 describes the struggle of a mother in pregnancy, giving birth to raising. God tells the strugglr of a mother so that a child can know a motherâ€™s struggle so that he can reply by doing good to him and not lawless to him even on of them do not say â€œahâ€ which has been described in surah Al â€" Isra verses 23-24. In the letter of Al-Isra verses 23-24 it consists of five kinds of prohibitions in the words of Uffin, the ban forming with harsh words, saying with noble words, be tawadhu, and pray for his parents either alive or dead. Al â€" Qurâ€™an and sunna assert Birrul Walidain as a duty. This explains how big the attention of Islam to both parents.